2009
DOI: 10.1177/0037768609338764
|View full text |Cite
|
Sign up to set email alerts
|

Toward a Contextualized Concept of Civil Religion

Abstract: A new definition of civil religion is needed because there are almost as many definitions as there are writers on the subject. By combining two existing concepts it can be shown that most existing definitions of civil religion are related. The two concepts are religious pluralism versus monoculture and public versus private religion. The first takes into consideration that civil religion will look different in a mono-religious country than in a multi-religious country. The second makes a distinction between ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 20 publications
(26 reference statements)
0
7
0
Order By: Relevance
“…The wide-ranging discussions over what, exactly, civil religion is eventually led Bellah himself to lament the concept's muddied analytic usefulness (Bellah, 1980). Luchau (2009), in fact, has suggested that there are as many definitions of civil religion as there are scholars discussing it. This panoply of definitions renders a clear or essentialist definition of civil religion somewhat challenging, as there is no shortage of concepts to sift through.…”
Section: Definitional Debatesmentioning
confidence: 99%
See 3 more Smart Citations
“…The wide-ranging discussions over what, exactly, civil religion is eventually led Bellah himself to lament the concept's muddied analytic usefulness (Bellah, 1980). Luchau (2009), in fact, has suggested that there are as many definitions of civil religion as there are scholars discussing it. This panoply of definitions renders a clear or essentialist definition of civil religion somewhat challenging, as there is no shortage of concepts to sift through.…”
Section: Definitional Debatesmentioning
confidence: 99%
“…with divine -or otherwise ultimate -realities" (Moseley quoted in Hammond et al, 1994: 18). While Bellah specifically understood civil religion as involving reference to the nonoffensive presence of a divine being (i.e., God) and as serving an integrative role for society, these specific elements of civil religion have become less important to more recent conceptions (Luchau, 2009). Cristi and Dawson (1996) suggest that understandings of civil religion, at least in the American context, tend to view civil religion as 'existing quasi-independently' of both the state and church, focusing on a sacralized 'set of core values, like liberty, justice, charity and freedom,' being 'carried' by various rhetorics and rituals of the American polity and people.…”
Section: Definitional Debatesmentioning
confidence: 99%
See 2 more Smart Citations
“…In effect, we consider this national identity as the civil religion of Bangladesh. Luchau (2009) argues that civil religion as a concept mainly comes out of secularist principles. He points out that civil religion emerges as a solution to the problem of 'societal legitimization' and it is based on the assumption that institutional religions are no longer succeeding in legitimizing and/or integrating the current society.…”
Section: The Alternative Modelmentioning
confidence: 99%